Copper-chromium catalyst as well as synthesis method and application thereof

By using biological templates and co-flow reaction technology during the molding of copper chromium catalysts, a catalyst precursor with better compressibility and molding properties is formed, and mixed with graphite powder for tableting molding, the problems of difficulty in forming and low strength are solved, and the activity and selectivity of the catalyst are improved.

CN119869539APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311356190.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the molding process of the copper chromium catalyst, there are problems such as small powder compression ratio, poor fluidity, difficulty in forming, low strength, and many fragments. Additional additives, binders and lubricants are required, which shortens the catalyst life and increases corporate costs.

Method used

By mixing the solution containing copper and chromium sources with a biological template and reacting with the precipitant solution in a co-flow manner, a copper-chromium catalyst precursor is formed, and then mixed with graphite powder, and the copper-chromium catalyst is prepared by the tablet forming method.

Benefits of technology

The compressibility and molding properties of the catalyst are improved, the dependence on additives and binders is reduced, the high molding strength and low stack-specific density are maintained, and the activity and selectivity of the catalyst in the hydrogenation of dimethyl maleate preparation of 1,4-butanediol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869539A_ABST
    Figure CN119869539A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-chromium catalyst as well as a synthesis method and application thereof. The copper-chromium catalyst provided by the invention comprises the following components in percentage by weight: 30%-60% of CuO and 40%-70% of Cr2O3, the side pressure strength of the catalyst is 70 to 120 N / particle, and the bulk density of the catalyst is 170 to 190 g / 100 mL. The catalyst provided by the invention is used in a reaction for preparing 1, 4-butanediol through dimethyl maleate hydrogenation, and the performance of the catalyst in the aspects of activity, selectivity and the like can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic materials, and in particular relates to a copper-chromium catalyst and a synthesis method and application thereof. Background Art

[0002] Copper-chromium composite metal oxide (Cu-Cr-O) catalysts are widely used in the hydrogenation of dimethyl maleate (DMM) to produce 1,4-butanediol. Usually, copper-chromium catalysts are loaded into fixed-bed tubular reactors to catalyze gas-solid phase hydrogenation reactions. This type of heterogeneous reaction process requires not only high activity and selectivity of the solid catalyst, but also ideal micro-macrostructure and mechanical strength, so that it can resist damage to the catalyst caused by loading, heating, airflow, and reaction, prevent blockage of the reaction device, and affect heat transfer, so as to ensure the normal progress of the chemical reaction process.

[0003] Therefore, before actual use, solid catalysts usually have to undergo molding treatment to obtain a specific shape and size, so that they have a certain appearance, pore structure and mechanical strength. At present, the commonly used catalyst molding methods include tablet molding, extrusion molding, spray molding, rotation molding, oil molding, etc. Among them, tablet molding is simple to operate and can obtain a molded catalyst with uniform texture, consistent shape and good mechanical strength for use in fixed bed reactors. It is widely used in small tests and industrial production and is a molding method with application prospects.

[0004] CN105709760A discloses a method for preparing a Cu-Cr catalyst, wherein a copper-chromium mixed solution and an alkaline solution are used for co-precipitation in parallel, citric acid is added to the remaining copper-chromium solution, and co-precipitation is continued in parallel, the reaction temperature is increased by 10 to 30°C, the reaction pH is increased by 0.5 to 1.5, and then the reaction product solution is heated to gel and dry gel, ground into fine powder, and ethanol is added and ignited, and the combustion product is the copper-chromium catalyst. CN1182732A discloses a CuO-Cr2O3-Al2O3 catalyst, wherein firstly, Cu, Zn, and Al metal salts are dissolved in deionized water, stirred evenly, and then ammonia water is added to react until pH=5.0, the precipitate is collected by filtration, washing, and drying and roasting to obtain the catalyst. CN113426447A discloses a method for forming a high-strength copper-silicon catalyst. The copper oxide and silicon oxide catalyst precursors are washed and dried, and then rolled in a device with automatic adjustment of the rolling height to enhance the material properties. The specific gravity of the material is adjusted by the rolling time, and a high-strength copper-silicon catalyst that is not easily broken is obtained after granulation and tableting.

[0005] Although copper-based catalysts, especially copper-chromium catalysts, have high carbonyl hydrogenation activity and selectivity for target product alcohols, and thus have become the focus of current research, for the tableting preparation of copper-chromium catalysts, researchers usually discuss parameters such as the mechanical strength of the catalyst after tableting based on the tableting process, and few people explore the effects of the catalyst phase composition and micromorphology on tableting performance. During the tableting process, copper-chromium catalysts have problems such as small powder compression ratio, poor fluidity, difficult molding, low strength, and many broken pieces. Generally, additional additives, binders, lubricants, etc. are required, which shortens the catalyst life and increases enterprise costs. Summary of the invention

[0006] Aiming at the problem that copper-chromium catalyst powder has a small compression ratio and poor fluidity, which makes it difficult to press into tablets, a copper-chromium catalyst that is easy to form and a synthesis method and application thereof are provided. The copper-chromium catalyst synthesized by the method has a microsphere structure before forming. Compared with Cu-Cr irregular morphology metal oxides, the Cu-Cr bimetallic oxide prepared by the present invention has better compressibility and forming performance. The catalyst of the present invention is used in the reaction of preparing 1,4-butanediol by hydrogenation of dimethyl maleate, and can improve the performance of the catalyst in terms of activity and selectivity.

[0007] The first aspect of the present invention provides a copper-chromium catalyst, wherein the weight content of each component in the catalyst is as follows: CuO 30% to 60%, Cr2O3 40% to 70%; the lateral pressure strength of the catalyst is 70 to 120N / particle, and the bulk density of the catalyst is 170 to 190g / 100mL.

[0008] Furthermore, the catalyst is prepared by tableting. Preferably, the catalyst is cylindrical in shape with a diameter of 2 to 4 mm and a height of 3 to 4 mm.

[0009] The second aspect of the present invention provides a method for synthesizing the copper-chromium catalyst, comprising:

[0010] (1) mixing a solution containing a copper source and a chromium source with a bio-template, and controlling the bio-template concentration in the mixed solution to be 0.01 to 0.5 g / mL;

[0011] (2) reacting the mixture obtained in step (1) and a precipitant solution in a parallel flow manner, and after the reaction is completed, aging, filtering, washing, and drying to obtain a copper-chromium catalyst precursor;

[0012] (3) The catalyst precursor described in step (2) is calcined, then mixed with graphite powder, and pressed into tablets to obtain a copper-chromium catalyst.

[0013] Furthermore, the biological template in step (1) is selected from one or more of lotus pollen, sunflower pollen, rapeseed pollen, lotus pollen, and camellia pollen. The biological template is microspherical with a particle size of 20 to 50 μm.

[0014] Furthermore, preferably, the biological template may be pretreated before step (1). The pretreatment may be an ultrasonic treatment in the presence of a solvent, followed by drying. The treatment conditions are as follows: temperature 25-70°C, time 0.5-5.0h. The solvent is one or more of deionized water, low-carbon alcohol (low-carbon alcohol is selected from alcohols with a carbon number of 6 or less, preferably ethanol), and N,N-dimethylformamide, and the number of ultrasonic treatments is 3-6 times. The drying conditions are as follows: drying temperature is 25-80°C, and drying time is 6-24h.

[0015] Furthermore, in step (1), the copper source and the chromium source may be conventional soluble metal salts, such as at least one of nitrates and acetates. In the solution containing the copper source and the chromium source, the concentration of the copper source is 0.05 to 5.0 mol / L, and the concentration of the chromium source is 0.05 to 5.0 mol / L. The solvent used in the solution containing the copper source and the chromium source may be at least one of water, methanol, ethanol, N,N-dimethylformamide, etc.

[0016] Furthermore, the precipitant used in the precipitant solution in step (2) is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water. The solvent used in the precipitant solution is selected from one or more of methanol, ethanol, water, N, N-dimethylformamide (DMF). The precipitant solution is preferably ammonia water, and the mass concentration of ammonia water is 5% to 15%.

[0017] Furthermore, in step (2), the reaction conditions are: reacting at 25-80° C. for 0.5-5.0 h, and controlling the reaction pH value to 4.0-9.0.

[0018] Furthermore, in step (2), the aging conditions are as follows: react at 30-80° C. for 0.5-5.0 h, and control the reaction pH value to 4.0-9.0.

[0019] Furthermore, in step (2), the washing solvent used in the washing is one or more of deionized water, methanol, ethanol, and N,N-dimethylformamide, and the washing times are 3 to 6 times. The drying conditions are as follows: the drying temperature is 25 to 80° C., and the drying time is 6 to 24 hours.

[0020] Furthermore, the copper-chromium catalyst precursor obtained in step (2) is in the form of microspheres with a particle size of 20 to 50 μm.

[0021] Furthermore, in the copper-chromium catalyst precursor obtained in step (2), copper-chromium crystals are evenly distributed on the surface of the biological template in the form of particles with a particle size of 100 to 400 nm.

[0022] Furthermore, the calcination conditions in step (3) are as follows: the heating rate to the calcination temperature is 4-8°C / min, the calcination temperature is 300-500°C, the calcination time is 2-6h, and the calcination atmosphere is an oxygen-containing atmosphere, such as air.

[0023] Furthermore, the amount of graphite powder added in step (3) accounts for 1% to 5% of the mass of the catalyst precursor after calcination.

[0024] The third aspect of the present invention provides the use of the copper-chromium catalyst in the hydrogenation reaction of dimethyl maleate to prepare 1,4-butanediol.

[0025] Furthermore, the application includes: in the presence of hydrogen, dimethyl maleate is contacted with the catalyst to react and produce 1,4-butanediol.

[0026] Furthermore, the catalyst of the present invention needs to be reduced and activated before use, and the reducing gas is hydrogen, or a mixture of hydrogen and nitrogen, wherein the volume ratio of H2 / N2 is (1-10): (90-99), the reducing temperature is 220-300°C, and the reducing time is 6-24h.

[0027] Furthermore, the reaction conditions are as follows: reaction temperature 150-300°C, pressure 1-10 MPa, volume space velocity 0.1-2.0 h -1 , hydrogen / ester molar ratio is 100-300:1.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] 1. The template used in the catalyst synthesized by the method of the present invention does not require subsequent treatment steps such as adding acid or alkali, and the preparation process is simple and suitable for industrial production.

[0030] 2. The catalyst synthesized in the present invention only needs to add graphite as a lubricant in the subsequent molding process without adding other binders, and can still maintain a high molding strength at a lower year-on-year weight.

[0031] 3. The catalyst precursor prepared by the present invention has a microsphere structure after calcination, and has better compressibility and molding performance.

[0032] 4. The catalyst of the present invention has good mechanical strength and low bulk density, and has high selectivity and conversion rate in the reaction of preparing 1,4-butanediol by hydrogenation of dimethyl maleate. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a scanning electron microscope (SEM) image of the catalyst A1 precursor obtained in Example 1;

[0034] Figure 2 This is the SEM image of the unformed catalyst A1 obtained in Example 1;

[0035] Figure 3 This is the SEM image of the catalyst A2 precursor obtained in Example 2;

[0036] Figure 4 This is the SEM image of the unformed catalyst A2 obtained in Example 2;

[0037] Figure 5 This is the SEM image of the catalyst A3 precursor obtained in Example 3;

[0038] Figure 6 This is the SEM image of the unformed catalyst A3 obtained in Example 3. DETAILED DESCRIPTION

[0039] The present invention will be described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention.

[0040] In the present invention, the bulk density is measured by using an AL204 electronic balance and a 250 mL measuring cylinder from Mettler-Toledo Instruments (Shanghai) Co., Ltd.

[0041] In the present invention, the mechanical strength is measured by using the DLⅢ intelligent particle strength instrument of Dalian Chemical Research and Design Institute to measure the radial crushing force of the molded catalyst, the instrument range is 300N, and the accuracy is 0.1N. 10 samples are selected from the samples to be tested, the radial crushing force is measured, the maximum and minimum values ​​are removed, and the average value is taken as the radial mechanical strength of the catalyst.

[0042] Example 1

[0043] (1) copper nitrate and chromic anhydride are prepared in a copper:chromium molar ratio of 1:1 to prepare a metal salt solution, wherein the total concentration of metal ions in the solution is 2.0 mol / L, and lotus powder (microspherical, with a particle size of 20 to 50 μm) is added thereto, and the concentration of the bio-template in the resulting mixture is controlled to be 0.1 g / mL;

[0044] (2) The precipitant solution is a 10 wt% ammonia solution. The acid-base coprecipitation process is used to add the mixture obtained in step (1) and the precipitant solution in parallel. The reaction temperature is controlled at 30°C, the reaction pH is 7.0, and the reaction time is 2.0 hours. After the reaction is completed, the product is aged at 30°C for 2 hours, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12 hours to obtain a catalyst precursor. The scanning electron microscope image is shown in FIG. Figure 1;Depend on Figure 1 It can be seen that the precursor is a microsphere structure with a particle size of 20 to 50 μm. The particles with a particle size of 100 to 400 nm in the precursor are evenly distributed on the surface of the biological template;

[0045] (3) The catalyst precursor obtained in step (2) was placed in a muffle furnace for calcination. The calcination conditions were as follows: the heating rate to the calcination temperature was 5°C / min, the calcination temperature was 400°C, the calcination time was 4h, and the calcination atmosphere was air, to obtain an unformed catalyst A1; the scanning electron microscope image thereof is shown in Figure 2 ;Depend on Figure 2 It can be seen that the unformed catalyst A1 is in the shape of microspheres;

[0046] (4) The unformed catalyst A1 was mixed evenly with 3% by mass of graphite, and the mixture was automatically formed into cylindrical particles with a diameter of 3 mm, namely, formed catalyst A1, by a tablet press. The properties of the formed catalyst are shown in Table 1.

[0047] The catalyst prepared by the present invention is used for hydrogenation of dimethyl maleate to prepare 1,4-butanediol. The molded catalyst A1 is selected as the catalyst. Before the reaction, it is reduced with hydrogen. The reduction conditions are as follows: hydrogen pressure is 0.1MPa, reduction temperature is 270°C, and reduction time is 12h. After the reduction is completed, the reaction is carried out according to the following conditions: reaction temperature is 190°C; feed volume space velocity is 0.25h -1 ; H2 / ester molar ratio 200:1; reaction pressure 6.0 MPa, dimethyl maleate conversion rate 99.9%; 1,4-butanediol selectivity 85.7%.

[0048] Example 2

[0049] (1) copper nitrate and chromic anhydride are prepared into a metal salt solution in a copper:chromium molar ratio of 1:2, wherein the total concentration of metal ions in the solution is 3.0 mol / L, and rapeseed pollen (microspherical, with a particle size of 20 to 50 μm) is added thereto, and the concentration of the bio-template in the obtained mixture is controlled to be 0.1 g / mL;

[0050] (2) The precipitant solution is a 10 wt% ammonia solution. The mixture obtained in step (1) and the precipitant solution are added in parallel by an acid-base coprecipitation process. The reaction temperature is controlled at 30°C, the reaction pH is 7.0, and the reaction time is 2 hours. After the reaction is completed, the mixture is aged at 30°C for 4 hours, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12 hours to obtain a catalyst precursor; Figure 3 It can be seen that the precursor is a microsphere structure with a particle size of 20 to 50 μm. Particles with a particle size of 100 to 400 nm in the precursor are evenly distributed on the surface of the biological template.

[0051] (3) The catalyst precursor obtained in step (2) is placed in a muffle furnace for calcination. The calcination conditions are as follows: the heating rate to the calcination temperature is 6°C / min, the calcination temperature is 400°C, the calcination time is 4h, and the calcination atmosphere is air, to obtain an unformed catalyst A2; Figure 4 It can be seen that the unformed catalyst A2 obtained after calcining the precursor is in the shape of microspheres.

[0052] (4) The unformed catalyst A2 was mixed evenly with 3% by mass of graphite, and the mixture was automatically formed into cylindrical particles with a diameter of 3 mm by a tablet press, namely the formed catalyst A2. The properties of the formed catalyst are shown in Table 1.

[0053] The catalyst reduction conditions and reaction conditions were the same as those in Example 1. The conversion rate of dimethyl maleate was 99.5% and the selectivity of 1,4-butanediol was 83.8%.

[0054] Example 3

[0055] (1) copper nitrate and chromic anhydride are prepared in a copper:chromium molar ratio of 1:1 to prepare a metal salt solution, wherein the total concentration of metal ions in the solution is 2.0 mol / L, and lotus powder (microspherical, with a particle size of 20 to 50 μm) is added thereto, and the concentration of the bio-template in the resulting mixture is controlled to be 0.05 g / mL;

[0056] (2) The precipitant solution is a 10 wt% ammonia solution. The mixture obtained in step (1) and the precipitant solution are added in parallel by an acid-base coprecipitation process. The reaction temperature is controlled at 35°C, the reaction pH is 7.5, and the reaction time is 2.0 h. After the reaction is completed, the mixture is aged at 35°C for 2 h, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12 h to obtain a catalyst precursor. Figure 5 It can be seen that the precursor is a microsphere structure, and particles with a diameter of 100 to 400 nm in the precursor are evenly distributed on the surface of the biological template.

[0057] (3) The catalyst precursor obtained in step (2) is placed in a muffle furnace for calcination. The calcination conditions are as follows: the heating rate to the calcination temperature is 7°C / min, the calcination temperature is 400°C, the calcination time is 4h, and the calcination atmosphere is air, to obtain an unformed catalyst A3; Figure 6 It can be seen that the unformed catalyst A3 obtained after calcining the precursor is in the shape of microspheres.

[0058] (4) The unformed catalyst A3 was uniformly mixed with 3% by mass of graphite, and the mixture was automatically formed into cylindrical particles with a diameter of 3 mm, namely, the formed catalyst A3, by a tablet press. The properties of the formed catalyst are shown in Table 1.

[0059] The catalyst reduction conditions and reaction conditions were the same as those in Example 1. The conversion rate of dimethyl maleate was 99.1% and the selectivity of 1,4-butanediol was 84.2%.

[0060] Comparative Example 1

[0061] (1) copper nitrate and chromic anhydride are used to prepare a metal salt solution in a copper:chromium molar ratio of 1:1, wherein the total concentration of metal ions in the solution is 2.0 mol / L;

[0062] (2) The precipitant solution is a 10 wt% ammonia solution. The acid-base co-precipitation process is used to add the mixture obtained in step (1) and the precipitant solution in parallel. The reaction temperature is controlled at 30°C, the reaction pH is 7.0, and the reaction time is 2 hours. After the reaction is completed, the mixture is aged at 30°C for 2 hours, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12 hours to obtain a catalyst precursor;

[0063] (3) calcining the catalyst precursor obtained in step (2) in a muffle furnace under the following calcination conditions: a heating rate of 5°C / min, a calcination temperature of 400°C, a calcination time of 4h, and an air atmosphere to obtain an unformed catalyst B1;

[0064] (4) The unformed catalyst B1 was mixed evenly with 3% by mass of graphite, and the mixture was automatically formed into cylindrical particles with a diameter of 3 mm by a tablet press, namely, the formed catalyst B1. The properties of the formed catalyst are shown in Table 1.

[0065] The catalyst reduction conditions and reaction conditions were the same as those in Example 1. The conversion rate of dimethyl maleate was 96.5% and the selectivity of 1,4-butanediol was 86.6%.

[0066] Comparative Example 2

[0067] (1) copper nitrate and chromic anhydride are used to prepare a metal salt solution in a copper:chromium molar ratio of 1:1, wherein the total concentration of metal ions in the solution is 2.0 mol / L;

[0068] (2) The precipitant solution is a 10 wt% ammonia solution. The acid-base co-precipitation process is used to add the mixture obtained in step (1) and the precipitant solution in parallel. The reaction temperature is controlled at 30°C, the reaction pH is 7.0, and the reaction time is 2 hours. After the reaction is completed, the mixture is aged at 30°C for 2 hours, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12 hours to obtain a catalyst precursor;

[0069] (3) calcining the catalyst precursor obtained in step (2) in a muffle furnace under the following calcination conditions: a heating rate of 5°C / min, a calcination temperature of 400°C, a calcination time of 4h, and an air atmosphere to obtain an unformed catalyst B2;

[0070] (4) The unformed catalyst B2 was uniformly mixed with 3% by mass of graphite and 3% by mass of kaolin, and the mixture was automatically formed into cylindrical particles with a diameter of 3 mm by a tablet press, namely the formed catalyst B2. The properties of the formed catalyst are shown in Table 1.

[0071] The catalyst reduction conditions and reaction conditions were the same as those in Example 1. The conversion rate of dimethyl maleate was 94.9% and the selectivity of 1,4-butanediol was 86.2%.

[0072] Comparative Example 3

[0073] (1) copper nitrate and chromic anhydride are used to prepare a metal salt solution in a copper:chromium molar ratio of 1:1, wherein the total concentration of metal ions in the solution is 2.0 mol / L;

[0074] (2) The precipitant solution is a 10 wt% ammonia solution. The acid-base co-precipitation process is used to add the mixture obtained in step (1) and the precipitant solution in parallel. The reaction temperature is controlled at 30°C, the reaction pH is 7.0, and the reaction time is 2 hours. After the reaction is completed, the mixture is aged at 30°C for 2 hours, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12 hours to obtain a catalyst precursor;

[0075] (3) calcining the catalyst precursor obtained in step (2) in a muffle furnace under the following calcination conditions: a heating rate of 5°C / min, a calcination temperature of 400°C, a calcination time of 4h, and an air atmosphere to obtain an unformed catalyst B3;

[0076] (4) The unformed catalyst B3 was uniformly mixed with 3% by mass of graphite and 3% by mass of white cement, and the mixture was automatically formed into cylindrical particles with a diameter of 3 mm, namely, the formed catalyst B3, by a tablet press. The properties of the formed catalyst are shown in Table 1.

[0077] The catalyst reduction conditions and reaction conditions were the same as those in Example 1. The conversion rate of dimethyl maleate was 97.1% and the selectivity of 1,4-butanediol was 83.8%.

[0078] Comparative Example 4

[0079] (1) copper nitrate and chromic anhydride are prepared in a copper:chromium molar ratio of 1:1 to prepare a metal salt solution, wherein the total concentration of metal ions in the solution is 2.0 mol / L, and lotus powder (microspherical, with a particle size of 20 to 50 μm) is added thereto, and the concentration of the bio-template in the resulting mixture is controlled to be 0.1 g / mL;

[0080] (2) The precipitant solution is a 10 wt% ammonia solution. The acid-base co-precipitation process is used to add the mixture obtained in step (1) and the precipitant solution in parallel. The reaction temperature is controlled at 30°C, the reaction pH is 7.0, and the reaction time is 2 hours. After the reaction is completed, the mixture is aged at 30°C for 2 hours, filtered and separated, washed with deionized water for 6 times, and dried in an oven at 60°C for 12 hours to obtain a catalyst precursor. Figure 3 It can be seen that the precursor is a microsphere structure with a particle size of 20 to 50 μm. Particles with a particle size of 100 to 400 nm in the precursor are evenly distributed on the surface of the biological template.

[0081] (3) The catalyst precursor obtained in step (2) is placed in a muffle furnace for calcination. The calcination conditions are as follows: the heating rate to the calcination temperature is 2°C / min, the calcination temperature is 400°C, the calcination time is 4h, and the calcination atmosphere is air, to obtain an unformed catalyst B4; Figure 4 It can be seen that the unformed catalyst B4 obtained after calcining the precursor is in the shape of microspheres.

[0082] (4) The unformed catalyst B4 was mixed evenly with 3% by mass of graphite, and the mixture was automatically formed into cylindrical particles with a diameter of 3 mm by a tablet press, namely the formed catalyst B4. The properties of the formed catalyst are shown in Table 1.

[0083] The catalyst reduction conditions and reaction conditions were the same as those in Example 1. The conversion rate of dimethyl maleate was 97.7% and the selectivity of 1,4-butanediol was 84.4%.

[0084] Table 1 Properties of the catalysts obtained in each example

[0085]

[0086] The embodiments of the present invention are only detailed descriptions of the technical solutions of the present invention, but the present invention is not limited to the above embodiments, that is, the present invention can be implemented without relying on the steps described in the above embodiments. In summary, any improvements made to the present invention by those skilled in the art, as long as they do not deviate from the content of the technical solutions of the present invention, any simple modifications, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention, shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A copper-chromium catalyst, wherein: The weight content of each component in the catalyst is as follows: CuO 30% to 60%, Cr2O3 40% to 70%; the lateral pressure strength of the catalyst is 70 to 120 N / particle, and the bulk density of the catalyst is 170 to 190 g / 100 mL.

2. The catalyst according to claim 1, characterized in that The catalyst is prepared by tabletting. Preferably, the catalyst is cylindrical with a diameter of 2 to 4 mm and a height of 3 to 4 mm.

3. The method for synthesizing the copper-chromium catalyst according to claim 1 or 2, comprising: (1) mixing a solution containing a copper source and a chromium source with a bio-template, and controlling the bio-template concentration in the mixed solution to be 0.01 to 0.5 g / mL; (2) reacting the mixture obtained in step (1) and a precipitant solution in a parallel flow manner, aging after the reaction, filtering, washing, and drying to obtain a copper-chromium catalyst precursor; (3) The catalyst precursor described in step (2) is calcined, then mixed with graphite powder, and pressed into tablets to obtain a copper-chromium catalyst.

4. The synthesis method according to claim 3, characterized in that In step (1), in the solution containing the copper source and the chromium source, the concentration of the copper source is 0.05 to 5.0 mol / L, and the concentration of the chromium source is 0.05 to 5.0 mol / L; and / or, the solvent used in the solution containing the copper source and the chromium source is at least one of water, methanol, ethanol, and N,N-dimethylformamide.

5. The synthesis method according to claim 3, characterized in that The biological template in step (1) is selected from one or more of lotus pollen, sunflower pollen, rapeseed pollen, lotus pollen, and camellia pollen. The biological template is microspherical with a particle size of 20 to 50 μm.

6. The synthesis method according to claim 5, characterized in that The precipitant used in the precipitant solution in step (2) is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water; the solvent used in the precipitant solution is selected from one or more of methanol, ethanol, water and N,N-dimethylformamide.

7. The synthesis method according to claim 3, characterized in that In step (2), the reaction conditions are as follows: react at 25-80°C for 0.5-5.0h, and control the reaction pH value to be 4.0-9.0; and / or, the aging conditions are as follows: react at 30-80°C for 0.5-5.0h, and control the reaction pH value to be 4.0-9.0; and / or, in step (2), the drying conditions are as follows: the drying temperature is 25-80°C, and the drying time is 6-24h.

8. The synthesis method according to claim 3, characterized in that The amount of graphite powder added accounts for 1% to 5% of the mass of the catalyst precursor after calcination; and / or, the calcination conditions are: the heating rate to the calcination temperature is 4 to 8°C / min, the calcination temperature is 300 to 500°C, the calcination time is 2 to 6h, and the calcination atmosphere is an oxygen-containing atmosphere.

9. Use of the catalyst according to any one of claims 1-1 or the copper-chromium catalyst prepared by any one of claims 3-8 in the reaction of hydrogenating dimethyl maleate to prepare 1,4-butanediol.

10. The use according to claim 9, characterized in that: The reaction conditions are as follows: reaction temperature 150-300°C, pressure 1-10 MPa, volume space velocity 0.1-2.0 h -1 , hydrogen / ester molar ratio is 100-300:1.

Citation Information

Patent Citations

  • Copper-chromium catalyst and its preparation method and use

    CN105709760A

  • Method for forming high-strength copper-silicon catalyst

    CN113426447A

  • Method for preparing 1, 4 -butanediol by gas phase hydrogenation

    CN1182732A